Ethylene and 1-Aminocyclopropane-1-carboxylate (ACC) in Plant–Bacterial Interactions - Nascimento, Francisco X.; Rossi, Márcio J.; Glick, Bernard R. (Frontiers in Plant Science, 2018)
Ethylene and its precursor 1-aminocyclopropane-1-carboxylate (ACC) actively participate in plant developmental, defense and symbiotic programs. In this sense, ethylene and ACC play a central role in the regulation of bacterial colonization (rhizospheric, endophytic and phyllospheric bacteria) by the modulation of plant immune responses and symbiotic programs, as well as by modulating several developmental processes, such as root elongation. Plant-associated bacterial communities impact plant growth and development, both negatively (pathogens) and positively (plant-growth promoting and symbiotic bacteria). Some members of the plant-associated bacterial community possess the ability to modulate plant ACC and ethylene levels and, subsequently, modify plant defense responses, symbiotic programs and overall plant development. In this work, we review and discuss the role of ethylene and ACC in several aspects of the plant-bacterial interactions. Understanding the impact of ethylene and ACC in both the plant host and its associated bacterial community is key to the development of new strategies aimed at increased plant growth and protection.